Tabitha - Leben an der Grenze: ein Beitrag zum Verständnis von Apg 9,36-43 - Erichsen-Wendt, Friederike (Biblische Notizen, 2005)
“Life at the border” is a compositional topic of Act 9:36-43. Transitions between Jewish and pagan culture, between urban civilization and the chaotic sea, between religiously mandated purity and actually unavoidable impurity, between (emerging) church structures and evolving networks, and ultimately between life and death are presented to the reader. The author makes use of Jewish religious traditions on the one hand (esp. the narration of Jonah), and local mythical traditions (Andromeda- Perseus myth) on the other. He refers to customary ritual (mourning rites) to interpret ethical-diaconical acting and at the same time to illustrate the neuralgic situation in which the Joppean Church, being in statu nascendi, found itself. Peter’s miraculous intervention and the local widows’ ongoing solidarity, which transgresses borders, together master the situation.